Emissions of CO and CH4 during Extreme Wildfires in the Pantanal - Neto, João Batista Ferreira (2024)
The Pantanal biome, representing the world's largest continuous floodplain, experienced a prolonged drought commencing in 2019 and intensifying in 2020. This condition led to natural disasters, culminating in the Pantanal wildfire crisis in 2020. Wildfires emit large quantities of gases and particles, with these emissions recognized as influential in the chemical composition of the atmosphere and the global climate system. Therefore, this study, employing remote sensing techniques, qualitatively and quantitatively investigates the spatial distribution and trends of carbon monoxide (CO) and methane (CH4) before, during, and after wildfire events in the Pantanal do Rio Negro State Park, located in the state of Mato Grosso do Sul, Pantanal biome. The results highlighted a significant increase in the concentration of these gases in the atmosphere, as well as providing insights into their spatial distribution and pyrogeographic patterns in the region.